2013
DOI: 10.1002/ange.201300942
|View full text |Cite
|
Sign up to set email alerts
|

Palladiumkatalysierte migratorische Insertion von Isocyaniden: eine neue Methode für die Kreuzkupplungschemie

Abstract: Seit der Entdeckung der Ugi‐Reaktion und ähnlicher Isocyanid‐ basierter Mehrkomponentenreaktionen sind Isocyanide wichtige Bausteine für die organische Synthese. In den letzten zehn Jahren fanden Isocyanide als vielseitige C1‐Bausteine in der Palladiumkatalyse eine neue Anwendung. Palladiumkatalysierte Reaktionen, die unter Isocyanidinsertion ablaufen, bieten ein enormes Potenzial für die Synthese stickstoffhaltiger Feinchemikalien. In diesem Kurzaufsatz werden alle erzielten Erfolge auf diesem neu entstehende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…To channel the reaction towards the planned pathway,c ompetitive insertion of 4a into the NÀHb ond of 3a,l eading to amidine,h as to be avoided. [10] While many transition metals promote this transformation efficiently, [11] we have recently shown that as ilver salt, because of its high alkynophilicity,p referred to coordinate to the triple bond of the propargylamine,t herefore inhibiting the N À Hi nsertion process. [12] To our delight, reaction of 3a and 4a in toluene in the presence of AgOTf indeed afforded the proline amide 5a (16 %) resulting from aformal 1,1-gem difunctionalization of the terminal alkyne.Systematic survey of reaction conditions [*] Dr.S .T ong, […”
mentioning
confidence: 84%
“…To channel the reaction towards the planned pathway,c ompetitive insertion of 4a into the NÀHb ond of 3a,l eading to amidine,h as to be avoided. [10] While many transition metals promote this transformation efficiently, [11] we have recently shown that as ilver salt, because of its high alkynophilicity,p referred to coordinate to the triple bond of the propargylamine,t herefore inhibiting the N À Hi nsertion process. [12] To our delight, reaction of 3a and 4a in toluene in the presence of AgOTf indeed afforded the proline amide 5a (16 %) resulting from aformal 1,1-gem difunctionalization of the terminal alkyne.Systematic survey of reaction conditions [*] Dr.S .T ong, […”
mentioning
confidence: 84%
“…We have no explanation for this surprising result. Various electron-withdrawing and electron-donating groups are tolerated at the R 1 position and afford the corresponding products in good yields (Table 2, entries [5][6][7][8][9][10]. The use of sterically more congested substrates is tolerated and does not deteriorate the yield or rate of the reaction (entries 8 and 9).…”
Section: Entrymentioning
confidence: 99%
“…This is quite remarkable considering that the isocyanide scope is often limited in imidoylative palladium catalysis and in many reactions only tertbutyl isocyanide works well. [5] A less reactive triazole possessing a phenyl group at the R 1 position also reacted with various isocyanides under the standard conditions (entries 18-21). We chose to use 10 mol% PdA C H T U N G T R E N N U N G (OAc) 2 as catalyst with a long reaction time (72 h) as standard conditions for the reactions with secondary isocyanides for convenience and to illustrate generality.…”
Section: Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…Theproline derivatives 5/8 are useful building blocks for the synthesis of conformationally constrained peptidomimetics [8] and are key structural units of anumber of pharmaceuticals. [10] While many transition metals promote this transformation efficiently, [11] we have recently shown that as ilver salt, because of its high alkynophilicity,p referred to coordinate to the triple bond of the propargylamine,t herefore inhibiting the N À Hi nsertion process. To channel the reaction towards the planned pathway,c ompetitive insertion of 4a into the NÀHb ond of 3a,l eading to amidine,h as to be avoided.…”
mentioning
confidence: 99%